Serum and urine headspace using electronic nose (e-nose) technology - Knobloch, Henri (Cranfield University, 2009)
For the last 20 years, several applications of electronic nose (e-nose) have been reported in the area of microbiology, environmental and agricultural monitoring or medical diagnosis. E-noses were used to detect contaminants or for quality control. However, little has been reported about complex methodological problems which are strongly linked to the e-nose performance. This thesis summarises various e-nose systems and alternatives for gas and headspace analysis, highlights the essential problems associated with e-nose analysis and explains why these devices have a potential for the detection of trace gas molecules but also why a stable and reliable analysis is not possible yet. Methodological weaknesses such as changes in mass flow rates, filter application or sampling methods are addressed. Understanding these enables analysis of serum and urine samples from cattle or badgers either naturally or experimentally infected with the zoonotic diseases caused by Mycoplasma bovis, Mannheimia haemolytica A1, Mycobacterium bovis, Mycobacterium avium ssp. paraTuberculosis and Brucella sp. The circumstances under which meaningful results can be obtained using the ST214 e-nose (Scensive Tech. Ltd., UK) are assessed which show the current limitations for discriminating between samples. Alternative methods for analysing e-nose data are mentioned and reasons are given why under the stated circumstances no straightforward multivariate statistics is possible. However, despite various difficulties, meaningful results at a group level were obtained and could be correlated with other results obtained using alternative analytical methods. This indicates the positive proof-of-principle character of this project.